2011
DOI: 10.1111/j.1365-2893.2011.01452.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the IFITM3 gene as an inhibitor of hepatitis C viral translation in a stable STAT1 cell line

Abstract: SUMMARY To investigate the functions of signal transducers and activators of transcription 1 (STAT1)-induced anti-hepatitis C viral (HCV) effects, a stable Huh7.5 cell line (Huh7.5-STAT1ER) was established that constitutively expresses a fusion protein (STAT1ER) of STAT1 and the mouse oestrogen receptor (ER), which forms STAT1ER homodimers after 4-hydroxytamoxifen (4-HT) treatment. This inducible and cytokine/receptor-independent STAT1 activation system allowed us to investigate the anti-HCV effects of STAT1ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 40 publications
2
27
0
3
Order By: Relevance
“…These authors showed that IFITM3 was induced by IL1 as well as by IFN-α and that over-expression of IFITM3 reduced HCV RNA abundance in replicon-bearing cells. How IFITM3 exerts its anti-HCV effect remains elusive, but it was recently reported that IFITM3 suppresses both cellular and HCV IRES-dependent translation (182). It should be noted, however, IFITM3 was reported not to inhibit HCV-N replicon in HEK293 cells (71).…”
Section: Isgs That Demonstrate Antiviral Activity Against Hcvmentioning
confidence: 99%
“…These authors showed that IFITM3 was induced by IL1 as well as by IFN-α and that over-expression of IFITM3 reduced HCV RNA abundance in replicon-bearing cells. How IFITM3 exerts its anti-HCV effect remains elusive, but it was recently reported that IFITM3 suppresses both cellular and HCV IRES-dependent translation (182). It should be noted, however, IFITM3 was reported not to inhibit HCV-N replicon in HEK293 cells (71).…”
Section: Isgs That Demonstrate Antiviral Activity Against Hcvmentioning
confidence: 99%
“…In Figure 5A, the 1-8U protein was detected by Western blotting and was up-regulated in Huh7.5-IRF3ER cells after 4-HT treatment. Due to auto-dimerization of IRF-3ER fusion protein in Huh7.5-IRF3ER cells, the fold-induction of 1-8U protein (Figure 5A, lane 1, 2, and 3) is not as robust as described in our previous report in which the STAT1 gene was activated [27]. Real-time quantitative reverse-transcription PCR was used to detect and measure hnRNP M mRNA expression in Huh7.5-IRF3ER cells.…”
Section: Resultsmentioning
confidence: 79%
“…Interestingly, the HCV NS5A protein has been proposed to impair OAS1 function, thus counteracting the antiviral effect of this pathway [120]. At least two members of the IFN-inducible transmembrane (IFITM) family, IFITM1 and IFITM3, are antiviral towards HCV in vitro [105, 121123]. IFITM1 blocks HCV entry by binding to and preventing the interaction between the HCV co-receptors CD81 and occludin at tight junctions in hepatocytes [122].…”
Section: The Products Of Isgs Can Restrict Hcv Infectionmentioning
confidence: 99%
“…IFITM1 blocks HCV entry by binding to and preventing the interaction between the HCV co-receptors CD81 and occludin at tight junctions in hepatocytes [122]. IFITM3 has been proposed to function as an anti-HCV ISG by impairing HCV IRES-mediated translation [123]. However, it could also affect the HCV life cycle by perturbing cholesterol- and lipid-related biology within the cell.…”
Section: The Products Of Isgs Can Restrict Hcv Infectionmentioning
confidence: 99%